Determination of EDTA in feed and premix formulations by HPLC-DAD. (15th May 2015) - Chiumiento, Francesco; D'Aloise, Antonio; Marchegiani, Francesca; Melai, Valeria
Highlights: Feed safety. 2002/657/EC validation. EDTA complexes. Ion-pair chromatography. Abstract: A simple analytical method for the quantitative determination of ethylenediaminetetraacetic acid (EDTA) in feed and premix formulations was developed and validated. The method involves an extraction with an acidic ferric chloride solution, to quantitatively convert EDTA species in the samples into the Fe(III)–EDTA complex, and its subsequent detection by Ion-Pair-Reversed Phase-High Performance Liquid Chromatography-Diode Array Detection (IP-RP-HPLC-DAD). A robust validation procedure was performed according to the Decision 2002/657/EC at concentrations ranging from 25 to 100 mg kg −1 on sample. Good recoveries (85.6–92.8%) were obtained; repeatability of the method was in the range of 1.3–8.0%, with an intermediate precision ranging from 6.0% to 8.6%, both of them expressed as relative standard deviation (RSD). No interfering species hindered the straightforward detection of EDTA. Hence, the proposed method can be adopted for an effective and rapid routine analysis of products for livestock.